Fundamentals of Organic Chemistry - McMurry, John; Simanek, Eric (Australia : Thomson-Brooks/Cole, 2007)
Written for the short course-where content must be thorough, but to-the-point, FUNDAMENTALS OF ORGANIC CHEMISTRY, Sixth Edition, continues to provide an effective, clear, and readable introduction to the beauty and logic of organic chemistry. McMurry presents only those subjects needed for a brief course while maintaining the important pedagogical tools commonly found in larger books. With clear explanations, thought-provoking examples, and an innovative vertical format for explaining reaction mechanisms, FUNDAMENTALS takes a modern approach: primary organization is by functional group, beginning with the simple (alkanes) and progressing to the more complex. Within the primary organization, there is also an emphasis on explaining the fundamental mechanistic similarities of reactions. Through this approach, memorization is minimized and understanding is maximized. The sixth edition brings in new content that applies organic chemistry to students, for example all of the chapter openers have been changed and incorporate a model and photograph of an application of organic chemistry such as Taxol from the pacific yew tree. The book introduces a running application in the Interlude boxes and in the problems relating agricultural chemicals intended to unify the subject further for students. All of the problems have been reorganized by topic to make easier to assign and review. New problem categories have been added. The new problem categories are "In the Field with Agrochemicals" and "In the Medicine Cabinet" to reinforce the focus on applications.
Structure and bonding, acids and bases -- Nature of organic molecules -- Nature of organic reactions, alkenes -- Reactions of alkenes and alkynes -- Aromatic compounds -- Stereochemistry -- Alkyl halides -- Alcohols, phenols, and ethers -- Aldehydes and ketones, nucleophilic addition reactions -- Carboxylic acids and derivatives -- Carbonyl alpha-substitution reactions and condensation reactions -- Amines -- Interlude, the road map of chemical reactions -- Structure determination -- Biomolecules, carbohydrates -- Biomolecules, amino acids, peptides, and proteins -- Biomolecules, lipids and nucleic acids -- Organic chemistry of metabolic pathways -- Appendixes: Nomenclature of polyfunctional organic compounds; Glossary; Answers to selected in-chapter problems.
Includes index.
Keywords: CHEMISTRY, ORGANIC